Biochemical profile of bile fluid in patients with malignant cholestasis in comparison with cholestasis due to biliary stone - Hassan Teheri; Naser Ghaemian; Yaser Taghavi; Javad Shokry- Shirvani (Babol University of Medical Sciences, 2015)
Background: Cholangiocarcinoma is an invasive biliary malignancy with poor prognosis. Diagnostic accuracy of conventional methods is low which is mainly due to the specific anatomy of the disease. The aim of this study was to evaluate the diagnostic value of biochemical profile and tumor marker of the bile in patients with malignant cholestasis compared to that of choledocholithiasis. Methods: In this cross-sectional study, 46 patients with extrahepatic cholestasis were enrolled (20 patients with malignant cholestasis and 26 patients with choledocolithiasis) A definitive diagnosis of cholangiocarcinoma was made by imaging, cytology and biopsy. Bile fluid was obtained by aspiration through endoscopic retrograde cholagiopantreatography (ERCP) catheter or percutaneous drainage in patients with choledocolithiasis and cholangiocarcinoma respectively. Sex and age were matched in two groups. Data regarding the biochemical profile (triglyceride, (TG), cholesterol, billirubin and HDL) and CA19.9 level of the bile fluid were collected, then using the SPSS software, the data were analyzed. Results: Bile fluid level of TG, cholesterol, high - density lipoprotein (HDL), direct bilirubin and CA19.9 were significantly higher in patients with benign cholestasis in comparison with malignant cholestasis (P<0.001, P<0.001, P<0.001, P=0.012 and P= 0.03, respectively). Conclusion: Our study showed that the CA19.9 level of bile fluid in extrahepatic cholestasis due to biliary stone was significantly higher than those with cholangiocarcinoma, as is the biliary level of TG, cholesterol, high-density lipoprotein (HDL) and direct bilirubin. Thus they may help in the differentiation of benign versus malignant extra hepatic cholestasis.